Tanggung Jawab Influencer dalam Iklan Endorsement: Perspektif Perlindungan Hukum Konsumen - Hasna, Nabila; Yunita, Ani (Media of Law and Sharia, 2025)
New Media is a term defined modern advertising emerge from technological development, one of them is endorsement. Endorsement brings negative effects beside its advantages such as massive spread of misinformation which led to consumer’s loss. There is no specific regulation organized endorsement practices in Indonesia. This empirical study aims to analyse available legal protection of consumers, and to identify the legal remedies to hold parties accountable. The results shows that both preventive and repressive legal protection is embedded in various legal instruments. These instruments regulate business actors’ obligations, prohibit misleading practices, and establish standards of advertising. Influencers may comply with these provisions by conduct double checking procedures and ensure that advertisement is aligned to legal standards. Repressive legal protection is also provided under the same legislative framework, which sets out the liability of business actors and prescribes administrative and criminal sanctions for violations. In seeking redress, consumers may pursue non-litigation mechanisms by lodging complaints to influencers, business actors, or relevant authorities such as Komdigi, BPOM, BPKN, BPSK, or LPKSM. If the non-litigation mechanism does not work out, consumers may pursue litigation mechanism by filing lawsuits in courts within their domicile